The Technique of Storage of Meranti Balau (Shorea seminis (de Vriese) Sloot) - Muhammad Zanzibar; Naning Yuniarti; Ratna Damayanti Sianturi (Jurnal Perbenihan Tanaman Hutan, 2019)
The problem faced by meranti balau (Shorea seminis (de Vriese) Sloot) seed is the recalcitrant seed character so that the viability of the seeds rapidly decreases during the storage. The purpose of this research was to determine the best storage technique for meranti balau seed. This research was used factorial randomized complete design with three factors, namely the storage container factor (calico cloth and calico cloth in a wooden box), the storage room factor (ambient and AC), and the storage period factor (0 day, 3 days, 6 days, 9 days, 12 days, 15 days and 18 days). Each treatment consisted of 25 seeds, repeated 4 (four) times. The observed responses in this research were moisture content, germination percentage, and germination value. The results showed that the container, the storage room, and period of storage influenced the seed moisture content, germination percentage and germination value. The best storage technique is to use a container of calico cloth in a wooden box inserted into the ambient room condition. The interaction of the container of calico cloth in a wooden box with the ambient room can reduce the rate of meranti balau seed deterioration during storage.